2012
DOI: 10.1080/00219266.2012.716778
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS content knowledge and presentation strategies in biology for effective use in everyday life

Abstract: HIV/AIDS education should empower students to create knowledge using everyday life experiences. Such knowledge should then be used to construe experience and resolve social problems such as risk behaviour that leads to infection. In South Africa, attempts to reduce the spread of HIV include incorporating HIV/AIDS education in the Biology curriculum.However, there is a dearth of knowledge regarding the effectiveness of Biology-based HIV/AIDS education. The current study therefore aimed to identify strategies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Perhaps this could help alleviate the burden of HIV/AIDS, especially among the most vulnerable, such as women and children. Engaging learners in research activities in their local communities, as found in the present research, addresses concerns raised by Mnguni and Abrie (2012) in that HIV/AIDS knowledge can now be learned in the everyday context of the learners. This could, in turn, improve learners' ability to apply knowledge learned in school into their everyday lives (Chamany, Allen, & Tanner, 2008;Holbrook, 2014).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Perhaps this could help alleviate the burden of HIV/AIDS, especially among the most vulnerable, such as women and children. Engaging learners in research activities in their local communities, as found in the present research, addresses concerns raised by Mnguni and Abrie (2012) in that HIV/AIDS knowledge can now be learned in the everyday context of the learners. This could, in turn, improve learners' ability to apply knowledge learned in school into their everyday lives (Chamany, Allen, & Tanner, 2008;Holbrook, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…Previous research has shown that HIV/AIDS knowledge taught in school curricula does not always affect behaviors (Anderson & Beutel, 2007). Mnguni and Abrie (2012) suggest that this is probably because such knowledge lacks depth and is presented in a manner that is not relevant to students. Other scholars also argue that HIV/AIDS knowledge is presented in the Life Sciences CAPS curriculum as academic knowledge rather than functional knowledge (e.g., Wolff & Mnguni, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By not recommending this ideology therefore, teachers may not integrate socio-scientific issues in their teaching, which are meant to bridge the gap between science and society. It is perhaps for this reason that Mnguni and Abrie (2012) as well as Mnguni, Abrie and Ebersöhn (2016) found that in Life Sciences students are taught HIV/AIDS knowledge as "academic knowledge" rather than "functional knowledge". As a result, students fail to apply this knowledge in their behavioural practices related to HIV/AIDS.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…It is, therefore, imperative that the curriculum should respond to HIV/AIDS by providing learners with cutting-edge knowledge and skills required to deal with the socio-economic challenges caused by HIV/AIDS. The extent to which this is the case currently has been addressed by various scholars who suggest that the curriculum may not be playing a significant role in the fight against HIV/AIDS (e.g., Mnguni & Abrie, 2012;Mnguni, Abrie, & Ebersohn, 2016). The underlying cause of this misalignment between the curriculum and social needs has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%